Can the Target Set for Reducing Childhood Overweight and Obesity Be Met? A System Dynamics Modelling Study in New South Wales, Australia. (21st September 2018) - Roberts, Nick; Li, Vincy; Atkinson, Jo‐An; Heffernan, Mark; McDonnell, Geoff; Prodan, Ante; Freebairn, Louise; Lloyd, Bev; Nieuwenhuizen, Suzanne; Mitchell, Jo; Lung, Thomas; Wiggers, John
Abstract : The persistent prevalence of childhood overweight and obesity raises significant concerns about the impact on health, society and the economy. Responding to a target announced in September 2015 by the New South Wales (Australia) Premier to reduce childhood overweight and obesity by five percentage points by 2025, a system dynamics model was developed to support Government and stakeholders responsible for meeting the target. A participatory model building process, drawing cross‐sectorial expertise, was undertaken to estimate the individual and combined impact of interventions on meeting the target. The model demonstrated that it is theoretically possible to meet the target by implementing a comprehensive combination of policies and programmes. When limited to existing and enhanced population health interventions, the modelled result did not reach the target. The project provides an example of how participatory simulation modelling can combine a broad range of interventions together into likely scenarios and usefully inform government decision‐making. © 2018 The authors. Systems Research and Behavioral Science published by International Federation for Systems Research and John Wiley & Sons Ltd